Effect of different storage conditions on seed dormancy of SD20A and MD248 rice cultivars (Bioagro, 2020)
Rice seeds have little germination capacity during a certain period of time after being harvested. The evaluation of this phenomenon,  known  as  dormancy,  is  of  great  importance  given  its  incidence  in  the  establishment  of  the  crop.  With this objective, the seed behavior of cultivars SD20A and MD248 was evaluated under two storage temperatures (ST1 = 1-2 ºC; ST2 = 30-35 ºC) for seven time periods (SP; at approximately one-week intervals). There were differences in dormancy and germination for cultivars, ST, and SP. The initial germination percentage of SD20A (45 %) was notoriously higher than that of MD248 (2%), indicating a higher dormancy condition of the latter cultivar. The subsequent evaluations showed increases in germination and decreased dormancy of both cultivars in the two ST, being much higher in ST2, which evidenced a marked effect of temperature on the dormancy breakdown. The minimum level of germination required by Venezuelan regulations for all seed classes (≥ 80%) was reached by both cultivars only in ST2: at 24 days for SD20A and 35 days for MD248, reaching both cultivars germinations close to 100 % at the end of the trial (57 days). It is concluded that to promote dormancy breaking, storage at temperatures between 30 to 35 °C for at least 24 and 35 days are recommended for varieties SD20A and MD248, respectively.
Keywords: Germination; Oryza sativa; rice genotypes; temperature of storage